y/24=-24/18
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\dfrac{-4}{8}=\dfrac{x}{-10}=\dfrac{-7}{y}=\dfrac{z}{-24}\)
=>\(\dfrac{x}{-10}=\dfrac{-7}{y}=\dfrac{z}{-24}=\dfrac{-1}{2}\)
=>\(\left\{{}\begin{matrix}x=\left(-10\right)\cdot\dfrac{\left(-1\right)}{2}=5\\y=\dfrac{-7\cdot2}{-1}=14\\z=\dfrac{-24\cdot\left(-1\right)}{2}=\dfrac{24}{2}=12\end{matrix}\right.\)
b: \(\dfrac{-3}{6}=\dfrac{x}{-2}=\dfrac{-18}{y}=\dfrac{-z}{24}\)
=>\(\dfrac{x}{-2}=\dfrac{-18}{y}=\dfrac{z}{-24}=\dfrac{-1}{2}\)
=>\(\dfrac{x}{2}=\dfrac{18}{y}=\dfrac{z}{24}=\dfrac{1}{2}\)
=>\(x=2\cdot\dfrac{1}{2}=1;y=18\cdot\dfrac{2}{1}=36;z=\dfrac{24}{2}=12\)
\(x^3+y^3=\left(x+y\right)^3-3xy\left(x+y\right)\)
\(=24^3-3\cdot24\cdot18\)
\(=13824-1296\)
=12528
\(\dfrac{4}{x-6}=\dfrac{y}{24}=-\dfrac{12}{18}\)
\(x-6=\dfrac{4\cdot18}{-12}=-6\)
\(\Rightarrow x=0\)
\(y=\dfrac{24\cdot\left(-12\right)}{18}=-16\)
`4/(x-6)=(-12)/18`
`=>4/(x-6)=(-2)/3`
`=>2/(x-6)=-1/3`
`=>x-6=-6`
`=>x=0`
`y/24=(-12)/48=(-2)/3`
`=>3y=24=>y=8`
Vậy `x=0,y=8`
Ta có :
\(\frac{x}{-2}=-\frac{3}{6}\Rightarrow x=\frac{-3.\left(-2\right)}{6}=1\)
\(\frac{-18}{y}=-\frac{3}{6}\Rightarrow y=\frac{-18.6}{-3}=36\)
\(\frac{-z}{24}=-\frac{3}{6}\Rightarrow z=\frac{-3.24}{-6}=12\)
Vậy x = 1 ; y = 36 ; z = 12
Ta có : \(\frac{-3}{6}=\frac{x}{-2}\)=> \(\frac{1}{2}=\frac{x}{2}\) => x = 1
\(\frac{-3}{6}=\frac{-18}{y}\) => \(\frac{1}{2}=\frac{18}{y}\) => y = 36
\(\frac{-3}{6}=\frac{-z}{24}\) => \(\frac{1}{2}=\frac{z}{24}\) => z = 12
Vậy ......................
\(\dfrac{y}{24}=-\dfrac{24}{18}\\ \dfrac{y}{24}=-\dfrac{4}{3}\\ y=-\dfrac{4}{3}\cdot24\\ y=-32\)
nhanh